A provincial Russian town: images for insiders and outsiders. Issue 1 (2nd January 2016) - Radina, Nadezhda K.
Abstract : This article analyzes the image of a provincial Russian town in the communicative context – for the insiders and the outsiders. The analysis provides insight into the management of the town's brand and allows the evaluation of potential tourist location. The image of the territory (which forms the brand's basis) was reconstructed through the qualitative and quantitative content analysis of 515 unstructured focused interviews with the citizens of minor towns. The residents of a provincial Russian town form its image predominantly through nature (rivers, forests, the opportunities for hunting and fishing, etc.). The image of the town for the insiders (focused on the nature) varies considerably from the version for the others/the outsiders (where the town's nature, history and culture are integrated). Therefore, the town's branding for inner tourism may vary considerably from the brand aimed at international tourism.